Granulomatous interstitial nephritis - Shah, Shivani (Clin Kidney J, 2015)
Granulomatous interstitial nephritis (GIN) is a rare entity detected in ∼0.5–0.9% of all renal biopsies. GIN has been linked to several antibiotics such as cephalosporins, vancomycin, nitrofurantoin and ciprofloxacin. It is also associated with NSAIDs and granulomatous disorders such as sarcoidosis, tuberculosis, fungal infections, and granulomatosis with polyangiitis. Renal biopsy is critical in establishing this diagnosis, and the extent of tubular atrophy and interstitial fibrosis may aid in determining prognosis. Retrospective data and clinical experience suggest that removal of the offending agent in conjunction with corticosteroid therapy often results in improvement in renal function. We describe a patient with a history of multiple spinal surgeries complicated by wound infection who presented with confusion and rash with subsequent development of acute kidney injury. Urinalysis demonstrated pyuria and eosinophiluria, and renal biopsy revealed acute interstitial nephritis with granulomas. These findings were attributed to doxycycline treatment of his wound infection. This review explores the clinical associations, presentation, diagnosis, and treatment of this uncommon cause of acute kidney injury.